IDENTIFIKASI AKTIVITAS EKSTRAK ETANOLIK BUAH MANGGA (MANGIFERA INDICA L.) PADA MENCIT JANTAN (MUS MUSCULUS) SEBAGAI PRODUK IMUNOGLOBULIN (IGM) - Herwin, Herwin; Meilani, Meilani (Fakultas Farmasi UMI, 2016)
Mango fruit (Mangifera indica L) is a plant which grow in Indonesia and contain antioxidant as carotenoid (Vitamin A), vitamin C and also various phenolic compound. The aim of the investigation was to find out the activity of ethanol extract of mango fruit on male guinea pig (Mus musculus) as an immunoglobulin product. The test of immunomodulator was using hemagglutination antibody titer. The extracts were in concentration of 2%,4%,6%,8% and 10% administered orally 1 mL/30 g BW of the mouse which pre-immunized with 2% v/v red blood cells of the lamb. The results showed that the activity of the IgM in day seventh was raised in concentration extract 6% and 8% w/v while concentration extract 2% and 10% were the same to the control and the averages titer of immunoglobulin was 1/8, on the other hand concentration of the extract 4% was low in IgM activity was 1/4.